Evaluation of corneal endothelial parameters in patients with methamphetamine use disorder - Koc, Hakan; Simsek, Meltem Hazel; Akkus, Mustafa (BMC ophthalmology, 2025)
Purpose To determine the structure and properties of corneal endothelial cells in patients with methamphetamine use disorder. Material and method The cross-sectional study included 33 eyes of 33 patients with methamphetamine (meth) use disorder and 33 eyes of 33 healthy subjects. Mean cell density, coefficient of variation, hexagonality ratio, maximum cell area, normal cell area, minimum cell area, and mean cell area were evaluated by non-contact specular microscopy. The parameters recorded in each group were compared. Results The mean ages of the individuals in the meth and control groups were 32.36 ± 7.68 and 31.18 ± 4.79 years, respectively. The mean daily meth dose was 0.306 ± 0.154 g, mean weekly meth use was 2.70 ± 1.46 days, and mean total meth dose was 302.70 ± 296.04 g in the meth group ( p = 0.456). The mean corneal endothelial cell count (ECD) values were 2692.82 ± 372.52 in the Meth group and 2869.7 ± 261.31 in the control group ( p = 0.76). The mean coefficient of variation (CV) values were 30.76 ± 3.41 in the meth group and 29.21 ± 2.55 in the control group ( p = 0.042). Mean hexagonality ratio (%) (HEX) values were 57.73 ± 9.38 in the meth group and 57.88 ± 9.96 in the control group ( p = 0.949). A positive correlation was observed between CV and meth dose and duration of meth use ( p = 0.011, p = 0.000, respectively). Conclusion The results of our study indicate that the corneal endothelium is subjected to stress in patients with a methamphetamine use disorder. The CV value suggests that the usability of methamphetamine as a quantitative indicator in the evaluation of possible corneal endothelial toxicity is an area that needs to be supported by further research.